Weaving relations through ceramics in the first moments of the Era in the Southern Puna of Argentina - Gasparotti, Leticia Inés; Escola, Patricia Susana (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2020)
The results obtained from the analysis of the ceramic material from the Las Escondidas site (Miriguaca grove, Southern Puna Argentina) are presented with the objective of addressing the characteristics of the ceramic production of the first moments of the Formative (between ca. 2000 AP and 1700 AP), in order to try to investigate the social context in which this ceramic was produced and used. To do this, two stages of analysis are proposed, the first through the use of binocular magnifying glass and the second, through petrographic analysis. The results obtained allowed to establish the particular characteristics and the possible functionality of the ceramic repertoire, as well as to determine the composition of the pastes. We identified certain constant technological choices and an important homogeneity in the use of specific raw materials, which could not be correlated directly with the local geological environment. Subsequently, from the detailed petrographic description, this set could be compared with others previously analyzed, both from the southern Puna of Argentina and from other surrounding sectors, contributing to establish networks of relationships in which the objects were immersed in the first moments of the era.